Non-operative Management of C2 Vertebral Body Fracture: Case Series - Pokhrel, A; Paudel, Sushil; Adhikari, S; Kafle, Dinesh; Pokhrel, Rohit Kumar (Nepal Orthopaedic Association Journal, 2019)
Fractures of the second cervical vertebra (C2) are the most common cervical spine injury. The most common C2 fracture is the odontoid fracture. The fracture of C2 vertebral body is one of the rare findings and is commonly classified as vertical coronal, vertical sagittal, and transverse subtypes by Benzel. Although treatment guidelines for other C2 fractures are clear, there is insufficient evidence to support treatment guidelines for C2 body fractures. We present four case series of C2 body fracture managed non-operatively with external orthoses.